Microcircuit mechanisms involved in paired associative stimulation‐induced depression of corticospinal excitability. (14th August 2013) - Weise, David; Mann, Jakob; Ridding, Michael; Eskandar, Kevin; Huss, Martin; Rumpf, Jost‐Julian; Di Lazzaro, Vincenzo; Mazzone, Paolo; Ranieri, Federico; Classen, Joseph
Key points:   Repetitively pairing peripheral nerve stimulation with transcranial magnetic stimulation of the corresponding contralateral motor cortex at 10 ms (paired associative stimulation; PAS10) leads to centre‐depressant effects on corticospinal excitability in a short time window.   PAS10‐induced centre‐depressant effects are due to weakening of excitatory synapses between principal cortical neurons, but not those located on corticospinal neurons, or inhibitory synapses.   Inhibitory interneurons are gate‐keepers to producing centre‐depressant PAS effects. The same mechanisms appear to govern PAS10‐induced surround‐facilitatory effects.   We propose a model specifying the composition and laminar location of the involved microcircuit of PAS‐induced plasticity that may enhance its utility as a model of spike‐timing‐ dependent plasticity in humans. Abstract  Synaptic weight changes induced by temporal correlations between the spikes of pre‐ and postsynaptic neurons are referred to as spike‐timing‐dependent plasticity (STDP). Transcranial magnetic stimulation (TMS) induces long‐lasting effects on corticospinal excitability, if it is repetitively paired with stimulation of afferents from a corresponding contralateral hand region at short intervals (paired associative stimulation, PAS). PAS‐induced plasticity has been linked with synaptic STDP. We aimed to investigate which elements of the cortical microcircuitry sustain and govern PAS‐induced depression of corticospinal excitability in the target muscle representation (and enhancement of excitability in its functional surround). We show that the time window during which the interaction between both stimulus‐induced cortical events leads to immediate post‐interventional depression is short (<4.5 ms). The depressant PAS effects at the target representation were completely blocked by applying a subthreshold magnetic pulse 3 ms before the principal TMS pulse, even when the strength of the latter was adjusted to generate a motor‐evoked potential of similar amplitude to that with the unconditioned magnetic pulse. Epidural recordings from the cervical cord of a patient showed that under this condition late TMS‐evoked I‐waves remain suppressed. When the intensity of the TMS component during PAS was lowered – sufficient to allow activation of inhibitory neurons, but insufficient to activate corticospinal neurons – excitability of short‐latency intracortical inhibition remained unchanged. PAS‐induced facilitation in the functional surround followed the same pattern as the centre‐depressant effects. These findings may suggest that excitability‐depressant PAS‐induced effects are due to weakening of excitatory synapses between upper cortical layer principal neurons, but not those located on the corticospinal neuron, or inhibitory synapses. Inhibitory interneurons involved in short‐latency intracortical inhibition are gate‐keepers to producing centre‐depressant/surround‐facilitatory PAS effects. Based on these and earlier findings we propose a model specifying the composition and laminar location of the involved microcircuit of PAS‐induced plasticity that may enhance its utility as a model of STDP in humans.